Use of Technogenic Silica Fume and Brown Coal Semi-Coke in the Technology of Silicon Carbide - Anikin A. E.; Galevskiy G. V.; Rudneva V. V.; Galevskiy S. G.; Ilyashchenko D. P. Dmitry Pavlovich (2016, 2016)
Title screen